THE ECONOMY OF “ROSE” GEORGIA: LOWERING OR FADING? - SMIRNOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2007)
In the days of the Soviet Union, Georgia was one of the most flourishing Soviet republics due to its protected tea and wine market and its attractive Black Sea resorts. The breakup of the U.S.S.R., the opening by the FSU republics of their borders to broad imports following the “parade of sovereignties,” and wars within the country led to a sharp decline in Georgia’s economic indicators, but in recent years the situation has begun to improve (see Table 1). Nevertheless, living standards in Georgia remain low. Official unemployment is around 13% of the working age population.1 But independent experts believe2 that from 2003 to the beginning of 2005 unemployment rose by 20% toindicators, but in recent years the situation has begun to improve (see Table 1). Nevertheless, living standards in Georgia remain low. Official unemployment is around 13% of the working age population.1 But independent experts believe2 that from 2003 to the beginning of 2005 unemployment rose by 20% to around 47% of the working age population.3 Most large industrial enterprises remain at a standstill or operate at less than full capacity. During the years of independence, over 1 million people4 —the most employable and active part of the population—have left the country. A significant proportion of Georgia’s population subsists, for the most part, on remittance-es from relatives working abroad. Experts estimate the annual number of remittances from Georgian “guest workers” living in Russia alone at 1-2 billion. According to an IMF analytical report on the economic prospects of the Middle East and Central Asia, remittances from abroad in 2005 accounted for over 5% of Georgian GDP.5 The country’s Minister of State Ka-kha Bendukidze estimates this amount at 4% of GDP.